Analysing gender disparities in youth sports coaching: an international survey (FEMCoach project) - Dias, Vanessa; Calleja-Gonzalez, Julio; López-Ros, Víctor; Font-Lladó, Raquel; Arede, Jorge; Cunha, Leonardo; Douka, Stella; Rosa, Bruno; Pinto, Graça; Leite, Nuno (Frontiers in Psychology, 2025)
IntroductionThe issue of gender inequality has a significant impact on the sporting world, with a range of implications and consequences. In the field of coaching, women are confronted with inequity throughout their careers, which frequently has a detrimental impact. To gain a deeper insight into the under-representation of women in sport coaching, framing the Female Sport Coaching Training Programme (FEMCoach) project, an investigation was carried out to examine coaches' educational support. After reviewing the scientific literature, a survey was developed aiming to analyse the needs of women youth sports coaches in practice to design coaching educational programmes that promote gender equity in youth sports.MethodsThe present study collected and analyzed survey data from 463 coaches (45% women and 55% men) from 24 different countries, sports and competitive levels. Coaches completed a 40-question online survey, divided into seven topics: (1) sociodemographic data, (2) the inclusion environment for sports practice, (3) coach professional activities, (4) menstrual cycle, hormonal contraception and pregnancy/childcare, (5) barriers for females in sport, (6) coaches' courses, and (7) gender differences.ResultsSome differences were found between women and men coaches' perceptions regarding barriers or stigmas that women face in practice. Most women's [80% (±5%)] and approximately half of men's [54% (±5%)] believe that women coaches sometimes face discrimination and/or mistrust and most of the women's [78% (±6%)] and the majority of men's [64% (±5%)] recognize different opportunities for coaches between genders. Considering the presence of topics related to female biology in coaches' education process the majority of women [72% (±5%)] and men [63% (±5%)] considered that they were not approached enough, agreeing most of the coaches, women [92% (±3%)] and men [87% (±4%)], that coach education programmes should be more expanded to cover it. In open-ended questions coaches agreed that educational programmes can promote gender equality and mentioned a lack of contents related to equity, identity and female biology.DiscussionFinally, accepting the limitations, this survey study provides relevant contextual information and practical applications for coaching educational programmes targeting women coaches and athletes and insights for governing bodies and institutions to foster gender equality in coaching.